Constructing a Noise Propagation Model to Assesss Community Noise Levels Stemming From Road Traffic: The Case of Somerville, MA. - Walker, Erica. (2017)
Abstract: This thesis explores the relationship between road traffic noise and sleep patterns, high blood pressure, and annoyance in Somerville, Massachusetts. Road traffic noise is assessed using a noise propagation model and predicted average day, night, and 24 hour noise decibel levels are calculated at the homes of participants in an ongoing NIH study of the health effects of exposure to traffic exhausts in the Somerville area (n=204). Using these modeled noise values, spearman correlations are calculated to assess the relationship between residents' sleeping patterns, high blood pressure diagnoses, and overall annoyance to road traffic noise. Modeled noise levels show that residents living closest to major roadways are subjected to noise levels that are 36% higher than WHO standards. Correlation results find a significant and positive correlation between the modeled noise levels and resident annoyance towards road traffic noise.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Mary Davis.; Committee: Wig Zamore.; Keyword: Urban planning.